If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 * 6 = 28 Multiply 2 * 6 x + 12 = 28 Reorder the terms: 12 + x = 28 Solving 12 + x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + x = 28 + -12 Combine like terms: 12 + -12 = 0 0 + x = 28 + -12 x = 28 + -12 Combine like terms: 28 + -12 = 16 x = 16 Simplifying x = 16
| 15y^2+17y+2= | | X^4-6x^3+12x^2-8x=0 | | 4z^2+20z+21=0 | | 6y+3=30 | | 3*7+y=19 | | cos(2x)-7cos(x)-3=0 | | 6y^2-6y-8=0 | | 5(4+6n)=110 | | -6x^2-9x+3=0 | | 125=4x+3y | | 2m-5(m+2)=-3(m-5) | | x+(x+1)+(x+2)+(x+3)=106 | | 64x+16= | | 3(x^2)+7x-2=0 | | 0=19t^2-130t-190 | | -30+3b=7(5b-4) | | 3*5+y=19 | | 3m=6squred | | 7=z-4 | | 12y=8x+-84 | | 16=5n-8n | | 3-x/2=6-5x/7 | | 3*4+y=19 | | 3m=6Squared | | .7x-7=.3x-5 | | 2(7x+3)= | | 0.8r+7=0.7r+1 | | 4(1-7f)=20 | | y-17=-19 | | 2(4-3r)=3(r+1)+14 | | 6(2x-1)=4(x+3)+14 | | 6y-5+4y=28 |